Evaluation of Hemostatic Abnormalities in Canine Spirocercosis and Its Association with Systemic Inflammation. (21st October 2013) - Pazzi, P.; Goddard, A.; Kristensen, A.T.; Dvir, E.
<x xml:space="preserve">Abstract</x> Background Canine spirocercosis is caused by the nematode Spirocerca lupi and is characterized by esophageal fibro‐inflammatory nodules that may undergo neoplastic transformation. No sensitive and specific laboratory assays other than histopathology have been reported to differentiate non‐neoplastic from neoplastic disease. Hypothesis/Objectives Dogs with spirocercosis will have evidence of hypercoagulability based on thromboelastography (TEG)‐derived maximal amplitude (MA); increased MA will be correlated with increased acute phase protein (APP) concentrations (C‐reactive protein [CRP] and fibrinogen); increased MA and APPs will be exacerbated with neoplastic spirocercosis. Animals Thirty‐nine client‐owned dogs with naturally occurring spirocercosis and 15 sex‐matched healthy controls. Methods A prospective comparative study evaluating TEG, activated partial thromboplastin time, prothrombin time, antithrombin (AT) activity, platelet count and D‐dimer concentration, and APPs of dogs with non‐neoplastic (n = 24) and neoplastic (n = 15) spirocercosis compared to control dogs. Results Median MA was significantly increased in the non‐neoplastic group (P < .01) and neoplastic group (P < .01) compared to the controls. Both APPs were significantly increased in the neoplastic group compared to the non‐neoplastic and control groups. MA was strongly correlated with fibrinogen (r = 0.85, P < .001) and CRP (r = 0.73, P < .001). An MA >76 mm provided 96% specificity and 73% sensitivity for differentiation of disease state. Conclusions and Clinical Importance Canine spirocercosis is associated with increased TEG variables, MA and α, and decreased AT activity, which may indicate a hypercoagulable state seemingly more severe with neoplastic transformation. MA was correlated with APP in dogs with spirocercosis and can be used as an adjunctive test to support the suspicion of neoplastic transformation.